Black and white fused silica: modified sol-gel process combined with moth-eye structuring for highly absorbing and diffuse reflecting SiO2 glass - Brunner, Robert; Kraus, Matthias; Hirte, Johannes; Diao, Zhaolu; Weishaupt, Klaus; Spatz, Joachim P.; Harzendorf, Torsten; Trost, Marcus; Munser, Anne-Sophie; Schröder, Sven; Baer, Michael (Optics express, 2020)
Diffuse reflecting (white) and highly absorbing (black) fused silica based materials are presented, which combine volume modified substrates and surfaces equipped with anti-reflective moth-eye-structures. For diffuse reflection, micrometer sized cavities are created in bulk fused silica during a sol-gel process. In contrast, carbon black particles are added to get the highly absorbing material. The moth-eye-structures are prepared by block copolymer micelle nanolithography (BCML), followed by a reactive-ion-etching (RIE) step. The moth-eye-structures drastically reduce the specular reflectance on both diffuse reflecting and highly absorbing samples across a wide spectral range from 250 nm to 2500 nm and for varying incidence angles. The adjustment of the height of the moth-eye-structures allows us to select the spectral position of the specular reflectance minimum, which measures less than 0.1%. Diffuse Lambertian-like scattering and absorbance appear nearly uniform across the selected spectral range, showing a slight decrease with increasing wavelength.